DAMPAK KEBIJAKAN WORK FROM HOME TERHADAP KINERJA PEGAWAI PASCA PANDEMI COVID-19 - Novalia, Tia; Marlina, Lina (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2023)
Employee performance greatly influences the achievement of organizational goals. However, the Covid-19 pandemic has affected employee work patterns. During the Covid-19 pandemic, the Work From Home policy is one way to reduce the spread of the Covid-19 virus, especially in office environments. With this Work From Home policy, employees can work more flexibly from home. It is certainly hoped that this work flexibility can improve employee performance so that organizational goals can still be achieved even though the pandemic causes restrictions on community activities. However, after the Covid-19 pandemic was lifted from endemic status in June 2023, the Work From Home policy was still implemented in various offices because it was considered to have a positive effect on employee performance. This research aims to determine the impact of the Work From Home policy on employee performance after the Covid-19 pandemic, especially in the Directorate of Customs Facilities, Directorate General of Customs and Excise. This research uses quantitative methods with data collection methods through observation and surveys of employees within the Directorate of Customs Facilities, Directorate General of Customs and Excise. The research results show that the Work From Home policy has a good/positive impact on employee performance after the Covid-19 pandemic at the Directorate of Customs Facilities, Directorate General of Customs and Excise. WFH improves employee performance which is assessed based on improvements in performance indicators: work quality; quantity; punctuality; effectiveness; and independence.